A Critical Analysis of Social Media Influencers and their influence on consumer choices of Restaurants in Dubai - James, Alfred (2017)
The digital marketing scenario is changing rapidly. Social media has now become the top priority for marketers and there is now need to stand out among the social media noise. Social media influencer marketing is the new type of social media marketing that is being used by marketers to make more social media noise. It has become a good alternative to traditional platforms of marketing. The dissertation explores the effectiveness of social media influencer’s in influencing the consumers choices of restaurants in the Dubai region. In order to investigate this, existing litera-ture on consumer behaviour, consumer psychology, the buying decision process of consumers and theories on social media and social media influencers have been critical analysed. Social media influencer marketing is a relatively new field of research in Dubai and not much research has been done to assess the effectiveness of this form of marketing which is now widely popular among restaurants in the Dubai region. In the scope of this dissertation an interpretive research methodology has been used along with semi structured interviews who are social media influencers, consumers and restaurants brand managers based in the Dubai. The dissertation concludes by considering the various implications for the findings, taking into consideration the specific attributes to the Dubai region.